2016
DOI: 10.5539/ass.v12n5p167
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Satisfactions from Public Hospitals Services in Alkharj and Hotat Bani Tamim: A Comparative Study

Abstract: Patients' satisfaction at public hospitals is an integral part to any hospital in the world. In recent times, health care industry has restructured its services to give better health care services to the study on patients. The focus of the study on patient' satisfaction from public hospitals services in selected cities Alkharj and Hotat Bani Tamim of Riyadh regions, Saudi Arabia. In these two public hospitals from each city, we conducted a sample of two hundred nineteen patients including hospitals representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The high item reliability indicated that the replicability of the items would occur if these items were tested by other respondents of the same size (Bond and Fox, 2007). The item mean was set to 0.00 logit to ensure each of the organisations had a 50:50 chance of success in responding to the item to match their ability (Hussain et al, 2015;Intezar, Alotaibi and Abdallah, 2016). The OMNSQ was 1.01 and OZSTD was -0.2, close to the expected value of 1 and 0, respectively.…”
Section: Organisation and Item Reliabilitymentioning
confidence: 99%
“…The high item reliability indicated that the replicability of the items would occur if these items were tested by other respondents of the same size (Bond and Fox, 2007). The item mean was set to 0.00 logit to ensure each of the organisations had a 50:50 chance of success in responding to the item to match their ability (Hussain et al, 2015;Intezar, Alotaibi and Abdallah, 2016). The OMNSQ was 1.01 and OZSTD was -0.2, close to the expected value of 1 and 0, respectively.…”
Section: Organisation and Item Reliabilitymentioning
confidence: 99%